1993
DOI: 10.1152/ajpheart.1993.265.5.h1727
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic responses to paraventricular nucleus disinhibition with bicuculline in conscious rats

Abstract: The present study was undertaken to determine the hemodynamic responses associated with stimulation of the hypothalamic paraventricular nucleus (PVN). Male Sprague-Dawley rats (n = 21) were instrumented with guide cannulas directed bilaterally at the PVN, with an electromagnetic flow probe placed on the ascending aorta and with femoral venous and arterial catheters. Bicuculline methiodide (BMI, 2 mM) was infused bilaterally (100 nl/20 min) into the PVN region before and after treatment with the beta 1-adrenerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 0 publications
4
61
0
Order By: Relevance
“…Furthermore, parvocellular neurons of the PVN project to regions of the CNS that control sympathetic outflow (36), including the rostral ventrolateral medulla, the dorsomedial medulla, and the spinal intermediolateral cell column (26,36,39). Numerous studies support the concept that neuronal projections from autonomic neurons in the PVN can modulate the activity of sympathetic nerves (27,28). Such data demonstrate that the PVN is an important central site where information concerning the level of blood-borne ANG II is processed and may play a significant role in mediating the attenuated renal SNA response to acute VE when circulating ANG II is chronically infused.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, parvocellular neurons of the PVN project to regions of the CNS that control sympathetic outflow (36), including the rostral ventrolateral medulla, the dorsomedial medulla, and the spinal intermediolateral cell column (26,36,39). Numerous studies support the concept that neuronal projections from autonomic neurons in the PVN can modulate the activity of sympathetic nerves (27,28). Such data demonstrate that the PVN is an important central site where information concerning the level of blood-borne ANG II is processed and may play a significant role in mediating the attenuated renal SNA response to acute VE when circulating ANG II is chronically infused.…”
Section: Discussionmentioning
confidence: 99%
“…12 Recently, in our laboratory, we have observed that interventions that raise MCFP by approximately 1 mm Hg are also associated with an increase in CO of approximately 10% to 15%. 26,32 Thus, changes in MCFP can have a significant impact on CO. In the present study, we observed a difference in MCFP that ranged from 1.2 to 1.7 mm Hg, which is of sufficient magnitude to have significantly elevated CO.…”
Section: Discussionmentioning
confidence: 99%
“…autonomic parameters, such as blood pressure and heart rate (Martin et al, 1991;Martin and Haywood, 1993). The cellular populations in the PVH that are responsive to BMI microinjection have not yet been defined.…”
Section: Effects Of Gaba Antagonism On Pvh Activitymentioning
confidence: 99%